Analyse von Benutzeranforderungen von Service-Kompositionen mittels Modelchecking - Nickel, Tobias

An Approach for a Decision Support Systems to optimize Water Tanks in Water Supply Systems by combining Network Reduction, Optimization and Simulation - Hallmann, Corinna
Since the last two decades, the water consumption in Germany is decreasing, which causes the water tanks and pipes in a water supply system to work inefficiently. This paper proposes an approach for a decision support system, which helps to decide how to plan new water tanks and resize existing tanks in water supply systems. The approach uses a combination of network reduction, mathematical optimization and hydraulic simulation. The mathematical optimization model is a nonconvex Mixed Integer Quadratically Constrained Program (MIQCP), which is solved by a piecewise linearization. As this may lead to many binary variables and therefore high computational times, the size of the water supply system model is reduced before building the optimization model. By applying several network reduction techniques there may occur some hydraulic differences between the original network model and the reduced network model. To make sure that the solution obtained in the optimization process is feasible in the original water supply system, the solution is verified by a hydraulic simulation tool.

Assignments of Collaborative Rescue Units during Emergency Response - Wex, Felix; Schryen, Guido; Neumann, Dirk (International Journal of Information Systems for Crisis Response and Management)

Decision Modeling for Assignments of Collaborative Rescue Units during Emergency Response - Wex, Felix; Schryen, Guido; Neumann, Dirk (Proceedings of the 46th Hawaii International Conference on System Science)

Algorithms for Sensor Systems - 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics

Adding Capacity-Aware Storage Indirection to Homogeneous Distributed Hash Tables - Wette, Philip; Graffi, Kalman (Proceedings of the Conference on Networked Systems (NetSys))
Distributed hash tables are very versatile to use, as distributed storage is a desirable feature for various applications. Typical structured overlays like Chord, Pastry or Kademlia consider only homogeneous nodes with equal capacities, which does not resemble reality. In a practical use case, nodes might get overloaded by storing popular data. In this paper, we present a general approach to enable capacity awareness and load-balancing capability of homogeneous structured overlays. We introduce a hierarchical second structured overlay aside, which allows efficient capacity-based access on the nodes in the system as hosting mirrors. Simulation results show that the structured overlay is able to store various contents, such as of a social network, with only a negligible number of overloaded peers. Content, even if very popular, is hosted by easily findable capable peers. Thus, long-existing and well-evaluated overlays like Chord or Pastry can be used to create attractive DHT-based applications.

A Survey of Fuzzy Service Matching Approaches in the Context of On-The-Fly Computing - Platenius, Marie; von Detten, Markus; Becker, Steffen; Schäfer, Wilhelm; Engels, Gregor (Proceedings of the 16th International ACM Sigsoft Symposium on Component-Based Software Engineering)
In the last decades, development turned from monolithic software products towards more flexible software components that can be provided on world-wide markets in form of services. Customers request such services or compositions of several services. However, in many cases, discovering the best services to address a given request is a tough challenge and requires expressive, gradual matching results, considering different aspects of a service description, e.g., inputs/ouputs, protocols, or quality properties. Furthermore,in situations in which no service exactly satifies the request, approximate matching which can deal with a certain amount of fuzziness becomes necessary. There is a wealth of service matching approaches, but it is not clear whether there is a comprehensive, fuzzy matching approach which addresses all these challenges. Although there are a few service matchingsurveys, none of them is able to answer this question. In this paper, we perform a systematic literature survey of 35 (outof 504) service matching approaches which consider fuzzy matching. Based on this survey, we propose a classication,discuss how different matching approaches can be combined into a comprehensive matching method, and identify future research challenges.

A privacy-friendly Architecture for future Cloud Computing - Petrlic, Ronald; Sekula, Stephan; Sorge, Christoph (International Journal of Grid and Utility Computing)
We present a privacy-friendly architecture for a future cloud computing scenario where software licensing and software payment plays a major role. We show how digital rights management as a technical solution for software licensing can be achieved in a privacy-friendly manner. In our scenario, users who buy software from software providers and execute it at computing centres stay anonymous. At the same time, our approach guarantees that software licenses are bound to users and that their validity is checked before execution. Thus, DRM constitutes an incentive for software providers to take part in such a future cloud computing scenario. We employ a software re-encryption scheme so that computing centres are not able to build profiles of their users – not even under a pseudonym. We make sure that malicious users are unable to relay software to others.

A Local Heuristic for Latency-Optimized Distributed Cloud Deployment - Keller, Matthias; Pawlik, Stefan; Pietrzyk, Peter; Karl, Holger (Proceedings of the 6th International Conference on Utility and Cloud Computing (UCC) workshop on Distributed cloud computing)
In Distributed Cloud Computing, applications are deployed across many data centres at topologically diverse locations to improved network-related quality of service (QoS). As we focus on interactive applications, we minimize the latency between users and an application by allocating Cloud resources nearby the customers. Allocating resources at all locations will result in the best latency but also in the highest expenses. So we need to find an optimal subset of locations which reduces the latency but also the expenses – the facility location problem (FLP). In addition, we consider resource capacity restrictions, as a resource can only serve a limited amount of users. An FLP can be globally solved. Additionally, we propose a local, distributed heuristic. This heuristic is running within the network and does not depend on a global component. No distributed, local approximations for the capacitated FLP have been proposed so far due to the complexity of the problem. We compared the heuristic with an optimal solution obtained from a mixed integer program for different network topologies. We investigated the influence of different parameters like overall resource utilization or different latency weights.

A Distributed Approximation Algorithm for Strongly Connected Dominating-Absorbent Sets in Asymmetric Wireless Ad-Hoc Networks - Markarian, Christine; Meyer auf der Heide, Friedhelm; Schubert, Michael (Proceedings of the 9th International Symposium on Algorithms and Experiments for Sensor Systems, Wireless Networks and Distributed Robotics (ALGOSENSORS))
Dominating set based virtual backbones are used for rou-ting in wireless ad-hoc networks. Such backbones receive and transmit messages from/to every node in the network. Existing distributed algorithms only consider undirected graphs, which model symmetric networks with uniform transmission ranges. We are particularly interested in the well-established disk graphs, which model asymmetric networks with non-uniform transmission ranges. The corresponding graph theoretic problem seeks a strongly connected dominating-absorbent set of minimum cardinality in a digraph. A subset of nodes in a digraph is a strongly connected dominating-absorbent set if the subgraph induced by these nodes is strongly connected and each node in the graph is either in the set or has both an in-neighbor and an out-neighbor in it. We introduce the first distributed algorithm for this problem in disk graphs. The algorithm gives an O(k^4) -approximation ratio and has a runtime bound of O(Diam) where Diam is the diameter of the graph and k denotes the transmission ratio r_{max}/r_{min} with r_{max} and r_{min} being the maximum and minimum transmission range, respectively. Moreover, we apply our algorithm on the subgraph of disk graphs consisting of only bidirectional edges. Our algorithm gives an O(ln k) -approximation and a runtime bound of O(k^8 log^∗ n) , which, for bounded k , is an optimal approximation for the problem, following Lenzen and Wattenhofer’s Ω(log^∗ n) runtime lower bound for distributed constant approximation in disk graphs.

Revisiting IS Business Value Research: What we already know, what we still need to know, and how we can get there - Schryen, Guido (European Journal of Information Systems (EJIS))

A Deterministic Worst-Case Message Complexity Optimal Solution for Resource Discovery - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Proceedings of 20th International Colloqium on Structural Information and Communication Complexity (SIROCCO))
We consider the problem of resource discovery in distributed systems. In particular we give an algorithm, such that each node in a network discovers the add ress of any other node in the network. We model the knowledge of the nodes as a virtual overlay network given by a directed graph such that complete knowledge of all nodes corresponds to a complete graph in the overlay network. Although there are several solutions for resource discovery, our solution is the first that achieves worst-case optimal work for each node, i.e. the number of addresses (O(n)) or bits (O(nlogn)) a node receives or sendscoincides with the lower bound, while ensuring only a linearruntime (O(n)) on the number of rounds.

Exploring Intermediate Vocational Education and Training for 16-19 Year-olds in Germany and England - Higham, J. J. S.; Kremer, H.-Hugo; Yeomans, D. (The Architecture of Innovative Apprenticeship)

Lernen im Justizvollzug. Vorstellung und Grundidee des Modellprojektes TANDEM - Kremer, H.-Hugo; Beutner, Marc; Wirth, W. (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung - Konzepte zur beruflichen Bildung im Jungtätervollzug)

Berufsorientierung im Jungtätervollzug - Rahmenkonzept und übergreifenden Prinzipien - Kremer, H.-Hugo; Beutner, Marc (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung - Konzepte zur beruflichen Bildung im Jungtätervollzug)

myflux.eu - Ein Instrument zur Förderung von Zielorientierung, Reflexion und Verantwortung im Berufsorientierungsprozess von Jungtätern - Gebbe, M.; Kremer, H.-Hugo (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung - Konzepte zur beruflichen Bildung im Jungtätervollzug)

Stärkenbasierte Berufsorientierung im Jungtätervollzug - Kremer, H.-Hugo; Knust, S. (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung - Konzepte zur beruflichen Bildung im Jungtätervollzug)

Mit dem Tandem in die Zukunft - Eine Einschätzung aus berufs- und wirtschaftspädagogischer Perspektive - Kremer, H.-Hugo; Beutner, Marc (Berufsorientierung, Gewaltsensibilisierung und Kompetenzentwicklung - Konzepte zur beruflichen Bildung im Jungtätervollzug)

Influence of angular radiated ultrasound waves on the Schlieren tomogram - Olfert, Sergei; Claes, Leander; Henning, Bernd (Proceedings of the International Conference on Acoustics)

Relational semantics for full linear logic - Coumans, Dion; Gehrke, Mai; van Rooijen, Lorijn (Journal of Applied Logic)